Expectancy modulates pupil size both during endogenous orienting and during re‐orienting of spatial attention: A study with isoluminant stimuli. (1st April 2019) - Lasaponara, Stefano; Fortunato, Gianfranco; Dragone, Alessio; Pellegrino, Michele; Marson, Fabio; Silvetti, Massimo; Pinto, Mario; D'Onofrio, Marianna; Doricchi, Fabrizio
Abstract: We have recently demonstrated that when endogenous orienting of spatial attention is guided by central directional cues that reliably predict the position of lateral targets. Pupil Dilation (PDil) is higher as compared with directional cues that do not predict target position. These findings were interpreted as reflecting different levels of Locus Coeruleus‐Noradrenergic activity during endogenous orienting. In contrast to this, we were not able to highlight reliable differences between PDil responses to infrequent invalid targets that are associated with predictive cues and frequent invalid targets that are associated with non‐predictive ones. These null findings might have been due to the spurious influence of transitory changes in luminance at the moment of target presentation or to the short time window used for the analysis of target‐related changes in PDil. Here, we re‐explored cue‐ and target‐related changes in PDil using cue and target stimuli that were kept isoluminant to their background and long lasting cue and target periods for data recording and analysis. We fully replicate our previous cue‐related results and, in addition, we demonstrate that infrequent invalid targets in the predictive experimental condition evoke larger PDil as compared with frequent ones. Analyses with Linear Mixed Models highlighted that both during the cue and target period, higher levels of PDil were associated with slower reaction times. These findings confirm that PDil is a reliable marker of the expectancy components of endogenous cue‐related and exogenous target‐related orienting of spatial attention. Abstract : Pupil dilation (PDil) is an index of Locus Coeruleus‐Noradrenergic activity. We studied PDil during orienting of attention with isoluminant cues and targets. We show that when orienting is guided by central cues that predict the position of lateral targets, PDil is higher as compared with cues that predict target position at chance. We also show that infrequent invalid targets associated with predictive cues evoke larger PDil than frequent invalid targets associated with non‐predictive cues.